Catheter-related urinary nosocomial infections in intensive care units: An epidemiologic study in North of Iran - Mohammad-Sadegh Rezai; Masomeh Bagheri-Nesami; Attieh Nikkhah (Babol University of Medical Sciences, 2017)
Background: Urinary tract infection (UTI) is one of the most common infections in developing countries. The aim of this study was to investigate the incidence of nosocomial catheter- associated UTI and its related factors in hospitalized patients in intensive care units of hospitals affiliated to Mazandaran University of Medical Sciences, in 2014. Methods: This cross-sectional study was conducted on patients who were admitted in hospitals and urinary catheterization was performed for them. Beds of intensive care units were followed-up for the occurrence of catheter-associated UTI for 14 months. Data were analyzed using SPSS Version 16. Results: Our results showed that of the 1409 patients (11648 catheter - days), the incidence of catheter-related UTI was 18.2% (among 256 individuals) equals to 21.987 per 1,000 catheter - days. E. coli was the most important cause of UTI. The results show that the history of the underlying disease, duration of catheterization and perineal washing were significantly associated with the incidence of UTIs. Conclusion: The findings of this study show a high incidence of UTIs caused by catheters in ICU. The incidence of this infection increased hospital length of stay and hospital cost. It seems that the necessary use of urinary catheters and its reduced duration use can be effective in decreasing this incidence.